The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1080/14756366.2023.2195991
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of novel histone deacetylase (HDAC) inhibitors derived from β -elemene scaffold

Abstract: β -Elemene is the major active ingredient of TCM anticancer drug elemene extracts. To further improve its antitumor activity and poor solubility, a polar HDACi pharmacophore was incorporated its scaffold. Systematic SAR studies led to the discovery of compounds 27f and 39f , which exhibited potent inhibitory activity against HDACs (HDAC1: IC 50 = 22 and 9 nM; HDAC6: 8 and 14 nM, respectively). In cellular levels, 27f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…More recently, Gao and co-workers developed and synthesized novel HDAC inhibitors derived from the β-elemene scaffold [234]. β-elemene is specifically a sesquiterpene used in the treatment of lung cancer, pancreatic cancer, gastric cancer, breast cancer, bladder cancer, and malignant brain glioma [235][236][237][238][239][240].…”
Section: Molecular Modelingmentioning
confidence: 99%
“…More recently, Gao and co-workers developed and synthesized novel HDAC inhibitors derived from the β-elemene scaffold [234]. β-elemene is specifically a sesquiterpene used in the treatment of lung cancer, pancreatic cancer, gastric cancer, breast cancer, bladder cancer, and malignant brain glioma [235][236][237][238][239][240].…”
Section: Molecular Modelingmentioning
confidence: 99%
“…These results further affirmed that dual-targeting PARP1 and other proteins of interest could benefit in treating diseases. Our laboratory has been working on several HDACs-related projects, , as well as dual inhibitors involving HDACs . Literature search revealed that no PARP7/HDACs dual inhibitor has been reported to date.…”
Section: Introductionmentioning
confidence: 99%